IMPLEMENTASI METODE BERNYANYI LAGU KU JAGA DIRIKU TERHADAP PEMBENTUKAN JATI DIRI MELALUI PENDIDIKAN SEKS ANAK USIA 5-6 TAHUN DI PAUD KIDANG KENCANA - Nurul Makkiyyah; Siti Rodiah; Hj Ai Aisah (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2025)
Sex education for children should be introduced from an early age, particularly in Early Childhood Education Institutions (PAUD), to help shape a child's identity into one that is confident, independent, and responsible. Through the song I Take Care of Myself, children can more easily grasp lessons on sexuality in a fun and supportive environment. This study aims to explore identity formation through sex education for children aged 5-6 at PAUD Kidang Kencana using the method of singing the song I Protect Myself. Knowledge about sexuality must be taught to children from a young age. Motivated by the issue of children's limited understanding of sexual topics, the researcher conducted this study to foster self-identity through sex education. This research employs a qualitative method, with data collection techniques including observation, interviews, document analysis, and triangulation. The findings reveal the following: (1) The implementation of the song-singing method (I Take Care of Myself) in shaping identity through sex education for 5-6-year-olds at PAUD Kidang Kencana is closely tied to the Daily Lesson Plan (RPPH). The sex education planning outlined in the RPPH includes learning steps and time allocation. (2) Initially, the singing method was conducted merely as a singing activity without deeper explanation or structured learning. (3) The evaluation of the singing method measures developmental progress and follow-up actions, which are reported to parents during end-of-theme meetings. The positive impact of this method includes improved child development outcomes based on set indicators. Supporting factors in this study include parental upbringing and learning media. Meanwhile, obstacles in applying this method include children with learning delays and parents who do not participate in parenting activities.